2018
DOI: 10.3892/ol.2018.9399
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑133a downregulated EGFR expression in human non‑small cell lung cancer cells via AKT/ERK signaling

Abstract: MicroRNAs (miRNAs) may serve important roles in the regulation of human non-small cell lung cancer (NSCLC) cell growth and apoptosis. To the best of our knowledge, the present study was the first to explore the role of miRNA-133a/epidermal growth factor receptor (EGFR) in regulating NSCLC cell growth and apoptosis via the AKT/extracellular signal-regulated kinase (ERK) signaling pathway. It was determined that miRNA-133a expression was lower in NSCLC tissue than in the adjacent mucosae. Additionally, EGFR expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The over-expression of miR-133a in MCF-7 and MDA-MB-231 cells could decrease G2/S phase and interfere DNA synthesis through the EGFR/Akt signaling pathway [16]. MiRNA-133a induced NSCLC cell apoptosis and decreased cell proliferation via the EGFR/AKT/ERK signaling pathway [17]. In esophageal cancer, miR-133a could targeted EGFR, and thus promote cell apoptosis and radio-sensitivity via downregulating the MEK/ERK pathway [5].…”
Section: Mir-133a In Cell Proliferation and Apoptosismentioning
confidence: 99%
“…The over-expression of miR-133a in MCF-7 and MDA-MB-231 cells could decrease G2/S phase and interfere DNA synthesis through the EGFR/Akt signaling pathway [16]. MiRNA-133a induced NSCLC cell apoptosis and decreased cell proliferation via the EGFR/AKT/ERK signaling pathway [17]. In esophageal cancer, miR-133a could targeted EGFR, and thus promote cell apoptosis and radio-sensitivity via downregulating the MEK/ERK pathway [5].…”
Section: Mir-133a In Cell Proliferation and Apoptosismentioning
confidence: 99%
“…More recent studies have demonstrated that melatonin may also modulate the expression of non-coding microRNAs (or, miRNA), which modulate many aspects of tumor phenotypes in breast, liver and gastric cancers [21,22,23]. In fact, melatonin may modulate expression of specific microRNAs that function across multiple tumor types, such as miR-155, miR-133a and miR-21 [24,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Transmembrane‐4 L‐six family member‐1 (TM4SF1) was reported to affect cell proliferation and invasion by modulating the Akt/ERK/mTOR pathway in NSCLC . miRNA‐133a down‐regulates epidermal growth factor receptor expression in NSCLC via the AKT/ERK signaling pathway . Down‐regulation of fatty acid synthase (FASN) could markedly inhibit the expression of p‐AKT and p‐ERK in A549 cells, suggesting that FASN has an inhibitory effect on the biological functions of NSCLC cells .…”
Section: Discussionmentioning
confidence: 99%